2013
DOI: 10.1002/jez.1816
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low levels of light at night upon the endocrine physiology of western scrub‐jays (Aphelocoma californica)

Abstract: Florida scrub-jays (Aphelocoma coerulescens) in the suburbs breed earlier than jays in native habitat. Amongst the possible factors that influence this advance (e.g., food availability, microclimate, predator regime, etc.), is exposure to artificial lights at night (LAN). LAN could stimulate the reproductive axis of the suburban jays. Alternatively, LAN could inhibit pineal melatonin (MEL), thus removing its inhibitory influence on the reproductive axis. Because Florida scrub-jays are a threatened species, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 74 publications
3
29
1
1
Order By: Relevance
“…Indeed, light at night suppressed melatonin levels in the morning, and this change was associated with earlier onset of individual activity (Dominoni et al 2013c ). A similar study has tested the effect of low levels of light at night (0.3 lux) on the melatonin profiles of Florida scrub jays (Aphelocoma coerulescens), but has surprisingly shown opposite results compared to my work on blackbirds: jays that were exposed to light at night showed higher levels of melatonin than animals exposed to normal light:dark cycles (Schoech et al 2013 ). Future studies should try to explore the relationship between light intensity and physiology, especially melatonin, in the wild.…”
Section: Light Pollution and Daily Cyclesmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, light at night suppressed melatonin levels in the morning, and this change was associated with earlier onset of individual activity (Dominoni et al 2013c ). A similar study has tested the effect of low levels of light at night (0.3 lux) on the melatonin profiles of Florida scrub jays (Aphelocoma coerulescens), but has surprisingly shown opposite results compared to my work on blackbirds: jays that were exposed to light at night showed higher levels of melatonin than animals exposed to normal light:dark cycles (Schoech et al 2013 ). Future studies should try to explore the relationship between light intensity and physiology, especially melatonin, in the wild.…”
Section: Light Pollution and Daily Cyclesmentioning
confidence: 86%
“…Several studies have highlighted variation in daily as well as in seasonal rhythms of different bird species (Miller 2006b; Kempenaers et al 2010; Nordt and Klenke 2013; Dominoni et al 2014, although other environmental stimuli proper of urban areas might have confounded these results. Recently, quasi experimental approaches in the field (Titulaer et al 2012; Da Silva et al 2014 and controlled experiments under laboratory conditions (Schoech et al 2013; Dominoni et al 2013b ) have tested specific hypotheses about the effects of light at night on the daily and seasonal cycles of birds, which have included investigations on the physiological mechanisms underpinning the temporal responses of birds to light at night. Because light is the most important synchronizer of the avian circadian clock (Berson et al 2002 ) and a countless number of physiological process are under circadian control (Foster and Kreitzmann 2004 ), changes in the light environment at night are likely to affect the expression of several biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Exposed to LAN, the scrub‐jays had lower LH, E 2 , and T levels than the dark controls (Schoech et al. 2013). Campo et al.…”
Section: Discussionmentioning
confidence: 99%
“…2005; Schoech et al. 2013) remains speculative but may be linked to the high variability seen in T levels.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, circadian melatonin patterns were inhibited by low intensity night light levels (Brüning et al 2015). In contrast, a study on western scrub-jays (Aphelocoma californica) showed opposite effects of light at night: amplitude of melatonin was increased (Schoech et al 2013). Therefore, it is still largely unknown how activity patterns and melatonin levels relate to intensity of light at night.…”
Section: Introductionmentioning
confidence: 99%